THE MIXTURE OF JAVANESE AND ISLAMIC CULTURES IN “GAMBRUNGAN” AS MADIUN’S LOCAL TRADITION - ALFIAN, RENGGA LABIB (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Gambrung, Islamic Culture, Javanese Culture Gambrungan is a local tradition existing in Madiun, East Java. This art adopts Islamic and Javanese culture. Indegeneous people appreciate this art as a medium to teach Islamic values. The writer analyzes the mixture between two different cultures that are Javanese and Islamic culture based on the elements which refers to mixture of culture.  This study uses qualitative approach which refers to textual and cultural analysis. The data is taken from tembang and performance of Gambrungan.  The theory of syncretism is used in this skripsi.This study analyzes the mixture of Javanese and Islamic culture. It results that syncretism has 3 elements : (1) ethnomusicology, (2) ethnopoetics, and (3) performance. Ethnomusicology element is kendang and gambrung, ethnopoeticselement is tembhang, and performance element is the performance of gambrunganitself.The writer would like to give some suggestion for the next researcher who wants to conduct a similar research to find out other elements about cultural studies of Gambrungan or to use a different theory. The writer expects that the next research can be more complete and understandable to reveal the important things in it.